Consequences of brown bear viewing tourism: A review. (February 2017) - Penteriani, Vincenzo; López-Bao, José Vicente; Bettega, Chiara; Dalerum, Fredrik; Delgado, María del Mar; Jerina, Klemen; Kojola, Ilpo; Krofel, Miha; Ordiz, Andrés
Abstract: Many countries promote wildlife observation as part of ecotourism offerings. The brown bear Ursus arctos is among the most targeted species for ecotourism in North America and Europe, making it an ideal candidate to examine the consequences of wildlife viewing upon the species. As bear viewing often occurs in sensitive places where bears congregate for mating, rearing young and/or feeding, it is important to evaluate potential positive and negative effects of different viewing practices. Here we reviewed available information on bear viewing practices and their effects on bears, people and ecosystems. Behavioural, physiological and ecological aspects related to bears are reviewed from three different perspectives: ecotourism consequences for bears, direct bear-human interactions and social impacts of bear ecotourism. Because bear viewing can have positive and negative impacts on both bear populations and bear-human interactions, it is important to carefully evaluate every practice associated with bear viewing at a local scale. Because bear populations around the world have diverse population statuses and different management regimes, successful procedures and rules effective in one place do not guarantee that they will be adequate elsewhere. Effective management of bear viewing practices requires a better understanding of the consequences for bears, the mechanisms behind observed bear reactions to humans, and the results of bear habituation. Because inappropriate bear viewing practices can lead to processes such as food-conditioning and habituation, which can have serious consequences for both people and bears, regulations on bear ecotourism are urgently needed to minimize unintended consequences of bear viewing practices. Highlights: Brown bears are among the most targeted species for ecotourism. Ecotourism may impact bear behaviour, physiology and ecology. Bear ecotourism can also influence bear-human interactions. Bear ecotourism can impact bear conservation positively and negatively. Context-dependent management of bear ecotourism is urgently needed.